A Systems View of Vehicle Landmine Survivability. Issue 1 (March 2015) - Cimpoeru, S.J.; Phillips, P.; Ritzel, D.V.
The protection of vehicle occupants against landmines is a systems problem which must consider multiple failure paths that can lead to occupant injuries. The response of a vehicle to underbelly blast from a landmine can be divided into three categories: 1) hull response to an immediate external blast load; 2) internal vehicle dynamics; and 3) global vehicle motions. Vehicle survivability is a broad and complex topic which is discussed in these terms and examples of protective subsystem elements are included. This paper argues that decomposing a complex blast protection system into its components from a systems point of view should contribute to the enhanced survivability of vehicle occupants.